2005
DOI: 10.1097/01.brs.0000192236.92867.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Degeneration on the Biphasic Material Properties of Human Nucleus Pulposus in Confined Compression

Abstract: Swelling is the primary load-bearing mechanism in both nondegenerate and degenerate nucleus pulposus. Knowledge of the biphasic material properties of the nucleus pulposus will aid the development of new treatment strategies for disc degeneration aimed at restoring mechanical function of the intervertebral disc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
205
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(248 citation statements)
references
References 31 publications
23
205
1
Order By: Relevance
“…Specifically, studies have shown hypermobility at low loads 34 and altered viscoelastic properties including increased creep rate and deformation 35 in early degeneration, mechanical changes that are attributed to the reduction in nucleus glycosaminoglycan. 5,7,8,36 At 4 weeks postinjection, neutral zone modulus, range of motion, and creep were all altered in a manner consistent with the expected changes in a degenerating disc, and were altered to the same degree as observed after an equivalent ChABC injection in vitro. Further, both neutral zone modulus and range of motion were linearly correlated with nucleus glycosaminoglycan content 4 weeks postinjection-relationships that were identical to those determined in the absence of biologic activity.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 51%
“…Specifically, studies have shown hypermobility at low loads 34 and altered viscoelastic properties including increased creep rate and deformation 35 in early degeneration, mechanical changes that are attributed to the reduction in nucleus glycosaminoglycan. 5,7,8,36 At 4 weeks postinjection, neutral zone modulus, range of motion, and creep were all altered in a manner consistent with the expected changes in a degenerating disc, and were altered to the same degree as observed after an equivalent ChABC injection in vitro. Further, both neutral zone modulus and range of motion were linearly correlated with nucleus glycosaminoglycan content 4 weeks postinjection-relationships that were identical to those determined in the absence of biologic activity.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 51%
“…As shown by Johannessen et al for the NP [34] and Iatridis et al [31,32] and Gu et al [27] for the AF, these changes affect the biomechanical behavior of the disc. Due to the reduction of the proteoglycan content in the NP, the swelling capacity of the NP tissue decreases significantly; at the same time, due to breakdown of collagen, the permeability of the tissue increases.…”
Section: Matrix Changesmentioning
confidence: 91%
“…Within the nucleus pulposus, the water content was found to decrease from 5.8 gH 2 O/g dry weight at an age of 14 years (85 % volume fraction) to 3.3 gH 2 O/g dry weight at age 91 years (75 %) [66]. For the NP, primarily, a loss of proteoglycans was observed [7,34]. For the AF, a change in water content, although to a more limited extent in comparison with the NP, as well as collagen content is observed during ageing [7].…”
Section: Cellular and Matrix Changesmentioning
confidence: 95%
“…At low applied loads, the nucleus pulposus likely resists load directly, and also, through the developed pressure, distributes the applied force radially to create a circumferential resistance in the annulus fibrosus. As glycosaminoglycan content of the nucleus is reduced, a decreased swelling pressure and increased aggregate modulus 16 lead to an altered load sharing between the nucleus and annulus, and larger deformations may occur prior to annulus fibers being engaged and loaded. 6,43,44 On the other hand, the nucleus plays less of a role at high compressive and tensile loads: the annulus fibrosus resists the applied loads and is dominant in determining deformation behavior via both the developed circumferential hoop tension and also direct axial support by the annulus glycosaminoglycan and water network.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Mechanical alterations due to degeneration have been noted within each tissue region of the disc as well as in the elastic and viscoelastic response of the entire bone-disc-bone motion segment. [12][13][14][15][16][17][18] However, the quantitative relationships between altered biochemistry and mechanics remain rather unclear, as it is difficult to isolate the multiple biochemical changes occurring in human degeneration.…”
Section: Introductionmentioning
confidence: 99%